2018
DOI: 10.1111/weng.12348
|View full text |Cite
|
Sign up to set email alerts
|

A cluster analysis of attitudes to English in Germany and the Netherlands

Abstract: Although English is becoming increasingly entrenched in Western Europe, large‐scale comparative studies of attitudes among the general public to this development are scarce. We investigate over 4,000 Dutch and Germans’ attitudes towards English based on responses to an attitudinal questionnaire. Respondents saw English as a useful additional language, but not generally as a threat to their national language. Using k‐means, an unsupervised clustering algorithm, we identified two attitudinal groups per country. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Figures for other languages are much lower. Edwards (2016) and Edwards and Fuchs (2018) show, however, with large‐scale questionnaire studies that two groups have to be distinguished in the Netherlands: a group with a positive attitude towards English and a (much smaller) group with a negative attitude towards English. The former, consisting of younger higher educated urban Dutch residents, likes using English, uses it frequently, considers proficiency in English a benefit on the job market and sees it as an enrichment to their mother tongue, Dutch.…”
Section: Attitudes Towards Englishmentioning
confidence: 99%
See 1 more Smart Citation
“…Figures for other languages are much lower. Edwards (2016) and Edwards and Fuchs (2018) show, however, with large‐scale questionnaire studies that two groups have to be distinguished in the Netherlands: a group with a positive attitude towards English and a (much smaller) group with a negative attitude towards English. The former, consisting of younger higher educated urban Dutch residents, likes using English, uses it frequently, considers proficiency in English a benefit on the job market and sees it as an enrichment to their mother tongue, Dutch.…”
Section: Attitudes Towards Englishmentioning
confidence: 99%
“…The group with a negative attitude towards English is older, less educated, lives in rural areas and has a lower proficiency in English. According to Edward and Fuchs (2018), people belonging to the latter group in particular would protest against the use of English in education and organisations, and against the penetration of English loanwords into Dutch. They would be the members of Dutch associations that protest against Anglicisation, such as Ampzing Genootschap (Ampzing Society) and Stichting Taalverdediging voor behoud en herstel van het Nederlands (Language Defense Foundation for the Preservation and Restoration of Dutch).…”
Section: Attitudes Towards Englishmentioning
confidence: 99%
“…Yet, at the conscious rating level, language differences may disappear because language and emotion processing are sensitive to time and attention regulation (Opitz & Degner, 2012;Thoma, 2021). It is difficult to say if frame-switching induces automatic emotional reactions, but the theory certainly allows for language-dependent feelings because any language can trigger different attitudes and expectations (e.g., Edwards & Fuchs, 2018;Nederstigt & Hilberink-Schulpen, 2018). In sum, at least context and processing theory jointly lead to hypothesis H1: H1: Balanced simultaneous bilinguals are less sensitive in their automatic pupillary reactions when exposed to a German versus Lx emotional stimulus than unbalanced sequential bilinguals are.…”
Section: The Present Studymentioning
confidence: 99%
“…Previous studies have shown that attitudes towards individual languages influence a wide range of linguistic behaviors, including what languages people decide to learn (e.g., Gardner & MacIntyre, 1993 ), the frequency with which they use their languages (e.g., Edwards & Fuchs, 2018 ), and whether they transmit these languages to their children (e.g., Kircher, 2019 ; for a more detailed overview of the consequences of language attitudes, see Dragojevic et al, 2021 ).…”
Section: Language Attitudesmentioning
confidence: 99%